Properties of polystyrene concrete bricks with sawdust ash - Chua,, Mcfarlane Kang Wei (Universiti Malaysia Sarawak (UNIMAS), 2009)
This project was carried out to investigate the mechanical and durability properties of hardened polystyrene concrete bricks containing sawdust ash. In this study, polystyrene beads as lightweight aggregate are used to replace fine aggregate in the concrete mixture whereas sawdust ash is for replacement of cement. A total of 216 bricks with the size of 195 mm x 100 mm x 65 mm (length x width x height) were prepared. Six tests were carried out to investigate and compared the properties of polystyrene concrete bricks. The tests were compressive strength test, water absorption, sea water attack, weight and density, dimension and acid attack. The compressive strength of bricks was depended on the materials mixed and the ratio used. Although higher ash content decreased the strength of concrete, the test result indicated that sawdust ash can contribute strength to concrete at longer curing periods. The bricks tested in sea water were compared with the bricks tested in tap water. The result shows the bricks with low weight and density recorded high water absorption rate. Sawdust ash also influenced the water absorption as it is a good water absorbing materials. The bricks tested in sea water recorded lower compressive strength than bricks tested in tap water. The bricks tested in acid attack also show changes in physical properties such as appearance, weight and density and dimension. The changes of properties of polystyrene concrete bricks are much higher for high content of polystyrene beads and sawdust ash in the mix.